Risco de abuso sexual em pessoas com deficiência intelectual e contexto familiar sobre sexualidade - Ferrari, Isa Maria de Souza Fernandes (2016)
Although sexuality is a natural behavior when associated to people with intellectual disabilities, there are beliefs and myths on the subject, especially in the family, primarily responsible for the teaching of sex and protection abilities practices. Such beliefs influencethe conception of the subject and prevent such people to receive knowledge about sex and sexuality and can help to increase a person's risk to suffer sexual abuse. Therefore, it is considered appropriate to investigate the family's views on the sexuality of people with intellectual disabilities and also the perception of people with intellectual disabilities about sexual abuse risk situations. This study aims to: raise and analyze the perception of people with intellectual disabilities on risk situations of sexual violence; up and analyze the views of people with intellectual disabilities of family members about the sexuality of people with intellectual disabilities; verify and analyze the relationship between the perception of people with intellectual disabilities on risk situations of sexual violence and the conceptions of the family on the sexuality of people with intellectual disabilities. The participants were 18 individuals, including people with intellectual disabilities and their families. For data collection with the family we used a semi-structured interviews, in order to understand the conceptions of sexuality; with people with intellectual disabilities was applied a translation of "What If" Situation Test, in order to identify their perception about sexual abuse risk situations. The data obtained for the test were encouraging regarding the identification of the appropriate and inappropriate touch situations in accordance with the instrument, but the low score in other issues enhances vulnerability to such a population of sexual abuse. The results of the data collected with the family, from the interviews analysis indicated the need to broaden their knowledge about sexuality of people with intellectual disabilities, as the prevailing belief of the asexuality of these people, moreover, such family rarely talked or instructed people with intellectual disabilities about sex education or self-protection skills against sexual violence. It being understood that it is necessary to strengthen the family's knowledge and modify its practices regarding sexuality and sexual education so as not only to prevent the person with intellectual disabilities suffer some kind of sexual violence, as well as prepare it and support it for exercise consciously and fully of their sexual and reproductive rights.